Altered White-matter Tract Property in Adults with Attention-deficit Hyperactivity Disorder. (1st April 2022) - Chiang, Huey-Ling; Yang, Li-Kuang; Chen, Yu-Jen; Hsu, Yung-Chin; Lo, Yu-Chun; Tseng, Wen-Yih Isaac; Gau, Susan Shur-Fen
Highlights: Altered white matter property over the brain in adults with ADHD is undetermined. Altered SLF, fronto-striato-thalamocortical tracts, and callosal fibers in ADHD adults. Alteration in ILF, frontal aslant tract and perpendicular fasciculus was also noted. The microstructural property of SLF was correlated with hyperactivity-impulsivity. Abstract: Although altered microstructure properties of white-matter tracts have been reported in children with attention-deficit/hyperactivity disorder (ADHD), findings from relatively few adult ADHD studies are inconsistent. This study aims to examine microstructural property over the whole brain in adults with ADHD and explore structural connectivities. Sixty-four medication-naïve adults with ADHD and 81 healthy adults received diffusion spectrum imaging. Generalized fractional anisotropy (GFA), an index indicating microstructural property, was calculated stepwise among 76 white-matter tracts. With the threshold-free clustering weighted method, the segments with the largest group difference were selected, and mean GFA (mGFA) values were calculated. Adults with ADHD had increased mGFA values in the segments located in the left frontal aslant tract, the right inferior longitudinal fasciculus, and the left perpendicular fasciculus, and reduced mGFA values in the segments located in the right superior longitudinal fasciculus (SLF) I, the left SLF II, the right frontostriatal tracts from dorsolateral prefrontal cortex and the ventrolateral prefrontal cortex, the right medial lemniscus, the right inferior thalamic radiation to the auditory cortex, and the callosal fibers. Additionally, the mGFA value of the right SLF I segment was associated with hyperactivity-impulsivity symptoms. Our findings suggest that white-matter tracts with altered microstructure properties are located within the attention networks, fronto-striato-thalamocortical regions, and those associated with attention and visual perception in adults with ADHD.